Everyday occupational problems perceived by participants in a pain rehabilitation programme. (July 2013) - Persson, Elisabeth; Lexell, Jan; Rivano-Fischer, Marcelo; Eklund, Mona
Abstract Background: Knowledge of the diversity of occupational problems perceived by people with chronic pain is insufficient. Aims: To describe everyday occupational problems among patients with musculoskeletal pain enrolled in a pain rehabilitation programme, and to compare subgroups based on participant characteristics. Methods: The sample consisted of 152 men and women. Occupational performance was assessed with the Canadian Occupational Performance Measure (COPM). Other data were obtained from forms including sociodemographic variables and pain diagnoses. Major findings: The participants reported 706 prioritized everyday occupational problems categorized as self-care (37%), productivity (32%), and leisure (31%). Household management was the largest sub-category. Working, sitting, and cleaning the house were the specific occupational problems reported most frequently. Women reported significantly more occupations related to productivity and men reported more self-care occupations. Principal conclusion: Patients with pain have a wide range of occupational problems that need to be addressed, along with gender-specific needs.